Vitality of english language in comparison to other main languages among Malaysian Primary School Students - How, Soo Ying (2016)
Due to the previous British colonization, language contact in the local context is accentuated. The environment in the nation, be it the education system or the local speech communities, has encouraged bilingualism or multilingualism. The language syllabi in the school system has given recognition to the learning of two languages (English and Malay languages) in national school and the learning of three languages (Mandarin or Tamil, English and Malay languages) in national-type school. In this multilingual milieu, Malaysians in the early age are given selection and choices to use particular language in the various domains of use. As such, it is rather common to have Malaysians speaking at least three if not more languages. Bringing the attention to the English language, despite its status as the second most important language in the nation and is known as the second language, the language is gradually slanted towards a foreign language more than a second language (Platt & Weber, 1980; Nunan, 2003). Thus, it is of interest to examine the vitality of languages evident in the linguistic repertoire of Malaysians at the primary level of education as indicative of an early stage of the reflection of language vitality. Specifically, this study aims to determine the language vitality of the English language vis-à-vis the other Malaysian languages in view of the language experiences. Vitality is referred to as the strength of a language. Although the studies of language vitality is often linked to minority and indigenous languages, language vitality in the present study has broadened to encompass the main languages in the nation. A combined qualitative and quantitative methodological approach was employed. Data were collected through questionnaire to a sampling of primary level students from urban and rural areas. Interviews were also conducted with primary school teachers to obtain additional insights on the vitality issues. The construction of the instruments (questionnaire and interview protocol) was guided by vitality indicators – language preference, language dominance, language choice, language use, language attitude and motivation, language proficiency. The data were analyzed using SPSS software and NVIVO 10 software. Results showed that English has lower vitality as compared to Malay language, Mandarin, and Tamil among primary school students at such early stage in the learning of English. Results point to the dominance of Malay, Mandarin, and Tamil among these Malaysian students in the language experience. However, these school children have early awareness that English plays key part in terms of communication, financial gain and prestige. Moreover, it is discovered that there is vitality difference in English language between rural and urban setting. In the case of national-type Chinese and Tamil school students, the vitality of the English language in rural areas is lower than that in urban areas. However, among national school students, it is interesting to find out that there is no vitality gap bridging in English language stretching from rural to urban setting. National school students regardless of the location possess similar vitality perception, which is at moderate level. The present result raises the possibility that it might relate to their strong claim to the Malay identity more than other groups do. The study also identified possible higher vitality of English language in the later age, which is supported by the data from the interviews. From the interviews with the teachers, it is seen that there are many folds of the vitality of English language that it cannot be measured by scale let alone. It is found that social milieu (in the sense of urban area versus rural area), socio-economic background and language policies contribute to the differences in the experience of the English language among students and thus influencing the vitality of the language. Results and findings revealed varied indications of importance and values attached to languages and different dimensions of the vitality of the English language in the defined context of use.